Formation of cadmium sulfide nanoparticles mediates cadmium resistance and light utilization of the deep‐sea bacterium Idiomarina sp. OT37‐5b. (7th September 2020) - Ma, Ning; Sha, Zhongli; Sun, Chaomin
Summary: Heavy metal is one of the major factors threatening the survival of microorganisms. Here, a deep‐sea bacterium designated Idiomarina sp. OT37‐5b possessing strong cadmium (Cd) tolerance was isolated from a typical hydrothermal vent. Both the Cd‐resistance and removal efficiency of Idiomarina sp. OT37‐5b were significantly promoted by the supplement of cysteine and meanwhile large amount of CdS nanoparticles were observed. Production of H2 S from cysteine catalysed by methionine gamma‐lyase was further demonstrated to contribute to the formation of CdS nanoparticles. Proteomic results showed the addition of cysteine effectively enhanced the efflux of Cd, improved the activities of reactive oxygen species scavenging enzymes, and thereby boosted the nitrogen reduction and energy production of Idiomarina sp. OT37‐5b. Notably, the existence of CdS nanoparticles obviously promoted the growth of Idiomarina sp. OT37‐5b when exposed to light, indicating this bacterium might grab light energy through CdS nanoparticles. Proteomic analysis revealed the expression levels of essential components for light utilization including electron transport, cytochrome complex and F‐type ATPase were significantly up‐regulated, which strongly suggested the formation of CdS nanoparticles promoted light utilization and energy production. Our results provide a good model to investigate the uncovered mechanisms of self‐photosensitization of nonphotosynthetic bacteria for light‐to‐chemical production in the deep biosphere.